2015
DOI: 10.1007/s11368-015-1132-4
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus status and its sorption-associated soil properties in a paddy soil as affected by organic amendments

Abstract: Purpose Yet the transformation and contribution of amorphous aluminum and iron which are usually indicated as oxalateextractable forms (Al ox and Fe ox ) to phosphorus (P) sorption in paddy soils, under long-term organic amendments combined with alternating flooding and draining, were not fully understood. The aim of this study was to investigate the effects of organic amendments on P status and P sorption-associated attributes including Al ox and Fe ox in a paddy soil. Materials and methods We selected 26 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…P CaCl2 , P citrate , P HCl , P Ols , and P M3 were highly correlated with TP (r = 0.587, 0.393, 0.886, 0.655, and 0.763, respectively). Similar results were also found by Palmer-Felgate et al (2009), Yan et al (2013), and Yan et al (2015). Pizzeghello et al (2011) suggested that the different correlations obtained can be related to the ability of methods to extract different proportion of available P. It was suggested that the buffering capacity and affinity of P in noncalcareous soils was strongly associated with extractable Al (Daly et al, 2015), while in calcareous soils it may be associated with extractable Ca (McLaren et al, 2014).…”
Section: Extractionssupporting
confidence: 81%
“…P CaCl2 , P citrate , P HCl , P Ols , and P M3 were highly correlated with TP (r = 0.587, 0.393, 0.886, 0.655, and 0.763, respectively). Similar results were also found by Palmer-Felgate et al (2009), Yan et al (2013), and Yan et al (2015). Pizzeghello et al (2011) suggested that the different correlations obtained can be related to the ability of methods to extract different proportion of available P. It was suggested that the buffering capacity and affinity of P in noncalcareous soils was strongly associated with extractable Al (Daly et al, 2015), while in calcareous soils it may be associated with extractable Ca (McLaren et al, 2014).…”
Section: Extractionssupporting
confidence: 81%
“…Soil adsorption capacity could effectively inhibit the release of P into water (Cui et al 2017). On the one hand, the soil adsorption capacity of P is influenced by the presence of ions, such as amorphous Fe and Al minerals (Yan et al 2013;Yan et al 2015;Fei et al 2019). In fact, Kang et al (2009) and Yan et al (2017) indicated that the mechanism involving the increase of P adsorption in soils included the stable complexes formed between P and amorphous Fe and Al minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Iron (Fe 3+ ) is redox sensitive and reduces to Fe 2+ with the development of reducing conditions, subsequently releasing previously sorbed P into soil solution. Phosphorus release as a result of reductive dissolution of P bearing minerals has been reported in studies on flooded soils from wetlands (Lai & Lam, 2008;Liu et al, 2012;Maranguit et al, 2017), paddy soils (Li et al, 2017;Rakotoson et al, 2016;Yan et al, 2015) and floodplains (Loeb et al, 2008;Schonbrunner et al, 2012). Although Al is not redox sensitive, flooding-induced increase in pH can solubilise Al-organic matter-PO 4 (Al-OM-PO 4 ) complexes (Darke & Walbridge, 2000).…”
Section: Effect Of Redox On Phosphorus Solubilisationmentioning
confidence: 98%
“…Bai et al, 2017;Kumaragamage et al, 2020;Rapin et al, 2019;Shaheen et al, 2021). However, studies investigating the effect of flooding on P dynamics are mainly confined to paddy soils (Li et al, 2017;Yan et al, 2015), wetlands (Bai et al, 2017;Lai & Lam, 2008;Surridge et al, 2007) and floodplains (Loeb et al, 2008;Schonbrunner et al, 2012) where soils remain flooded for large parts of the year and therefore are likely to have microbial populations well adapted to the seasonal fluctuations in soil moisture content. Moreover, in soils experiencing repeated drying-wetting/flooding cycles aggregates may become slake resistant (Denef et al, 2001), thus lowering the risk of nutrient release due to breakdown of aggregates and exposure of new labile organic matter (OM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation